2013
DOI: 10.1177/1545968313491004
|View full text |Cite
|
Sign up to set email alerts
|

Does the Evaluation of Gait Quality During Daily Life Provide Insight Into Fall Risk? A Novel Approach Using 3-Day Accelerometer Recordings

Abstract: Accelerometer-derived measures based on 3-day recordings are useful for evaluating fall risk as older adults perform daily living activities in their everyday home environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
243
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 272 publications
(293 citation statements)
references
References 50 publications
23
243
2
4
Order By: Relevance
“…Previous work has shown that quality of gait metrics from three days of normal activity can identify elderly people at risk of falling as good as clinically based tests [9]. Being able to assess falls risk via wearable sensor use as patients go about their daily life would allow many more patients to be monitored, as opposed to patients only having their falls risk assessed upon a visit to a clinician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that quality of gait metrics from three days of normal activity can identify elderly people at risk of falling as good as clinically based tests [9]. Being able to assess falls risk via wearable sensor use as patients go about their daily life would allow many more patients to be monitored, as opposed to patients only having their falls risk assessed upon a visit to a clinician.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to assess falls risk via wearable sensor use as patients go about their daily life would allow many more patients to be monitored, as opposed to patients only having their falls risk assessed upon a visit to a clinician. While this previous work [9] shows that falls risk can be obtained from gait data from the home and community, there is a possibility that the additional knowledge of the external environment during certain gait events may allow for a more accurate falls risk prediction as well as giving clinicians powerful information to guide rehabilitation programs to reduce the chance of falling.…”
Section: Discussionmentioning
confidence: 99%
“…<Table 1 -see end of document> Measurement of gait during free-living is difficult when using inertial sensor-based wearables only due to the lack of contextual information. Thus, initial work to quantify free-living gait started at low macro resolutions of 60-seconds [42], progressing to 10-seconds [43] ensuring, with a degree of certainty, that steady state gait was measured due to the cyclical nature of inertial gait signals.…”
Section: Activity Recognition: Macro and Micro Gaitmentioning
confidence: 99%
“…While such measures can potentially be useful in aiding general weight loss and providing motivation for users to become more active, there is also a need to determine more detailed quality of mobility metrics [1]. Research in the mobility space has linked such detailed mobility metrics to important health related outcomes such as falls risk [2], Parkinson's disease [1,3], Multiple sclerosis score [4] and cerebral palsy gait assessment [5].…”
Section: Introductionmentioning
confidence: 99%